Permasalahan Kurikulum Bahasa Melayu Sekolah Menengah Kerajaan di Wilayah Yala, Thailand - Bukehmatee, Nurnee; Ummah, Ummul; Maso, Assumani (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2023)
This paper discusses the problems of the Malay language curriculum in Government Secondary Schools (SMK) in Yala Province, Thailand. This study uses a qualitative approach. Two methods of obtaining data were used, namely document analysis and interviews. This study was conducted with the aim of identifying the form of problems in the Malay language curriculum in government schools in the Yala Province. In addition, the researcher gave suggestions to overcome the problem of the Malay curriculum that can be a reference for government secondary schools in the Yala Province. The results of this study show that there are several problems in the Malay language curriculum in government secondary schools, namely the problem of drafting the syllabus, implementation, learning objectives, content and assessment. Steps to overcome the problem, the drafters need to think of plans and preparations that can help the relevant parties to enact a dynamic curriculum.